Research on Gear Modification Optimization Design of Dual Power Drive Gearbox - Zixuan Ge; Zhuzheng Xu (Jixie chuandong)
Taking a certain type of dual-power drive gearbox transmission system as the research object，through static simulation，the transmission error and tooth surface load of the gear pair at the input end of the power source A are analyzed. According to the gear pair modification method， the Romax software is used to carry out the research on the influence law of the modification parameters in the transmission error and tooth surface load. Based on this，through genetic algorithm， the gear comprehensive modification optimization design combining tooth profile modification and helical modification is carried out， and the gear pair before and after modification is compared and analyzed. The results show that the gear transmission error is obviously reduced after the modification， and the tooth surface load distribution is more uniform.